Sosialisasi Teknik Pembuatan Solid dan Liquid Kompos untuk Peningkatan Produksi Buah Melon di Desa Limpok Kabupaten Aceh Besar - Syafruddin, Syafruddin; Yusnizar, Yusnizar; Zaitun, Zaitun; Nurahmi, Erida (JURNAL PENGABDIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (JP3L), 2023)
The knowledge and skills of the Farmers Group and School Drop Out Youth in Limpok Village regarding the technique of making solid and liquid compost for increasing melon production were still limited. The purpose of this product-based service activity was to increase the knowledge and skills of partner groups regarding solid and liquid composting techniques for increasing melon production. The main obstacle in increasing melon production was the difficulty of availability and the high cost of chemical (inorganic) fertilizers. Besides, plants were very susceptible to various diseases. The implementation of the activities includes counseling, demonstration of techniques for making solid and liquid compost and application to melon plants. The target and outcome of the activity was to increase the knowledge and skills of partner groups regarding the production of environmentally friendly solid and liquid compost to increase melon production. The results achieved from this activities were that the target partner group was able to produce 5.000 kg of solid compost and 3.000 liters of liquid compost per production. Another outcome of the partner group was that they can increase their income by doing solid and liquid compost and melon businesses in a professional and sustainable